Body weight training intervention towards weight loss of adolescent with obesity problem during COVID-19 pandemic - Nourmayansa Vidya Anggraini; Diah Ratnawati; Ritanti Ritanti; Mustika Widiyastuti (Intelektual Pustaka Media Utama, 2023)
The COVID-19 pandemic has brought attention to the rising issue of sedentary behavior, which can lead to obesity. Obesity affects individuals of all ages, including children, adults, and the elderly. Obesity can have negative effects on adolescent body image. Several interventions, such as body weight training, have been shown to help obese adolescents lose weight. This paper proposes an investigation into the effectiveness of body weight training interventions as implemented by community nurses for weight loss in obese adolescents. The intervention involved three sessions per week over the course of four weeks and was administered to several obese adolescents. The results indicated that there was a weight loss of 3.7 kg for the first participant and 3.8 kg for the second participant over the four-week period. Statistical analysis using a paired t-test showed a p-value less than 0.005, indicating a significant effect of the body weight training intervention on weight loss in obese adolescents. It is hoped that community nurses can utilize body weight training as a useful intervention in helping obese adolescents achieve a healthy weight.